(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص: تهدف هذه الورقة البحثية الى تسليط الضوء على تسابق البنوك المركزية في التكيف مع الشكل الجديد للعملات الرقمية في ظل الاقتصاد المشفر، وكذا الآثار المترتبة عن اعتماد العملات الرقمية للبنك المركزي على السياسة النقدية، الوساطة المالية والاستقرار المالي. وقد اعتمدنا في دراستنا المنهج الوصفي التحليلي، وخلصنا الى نتائج أهمها ضرورة تحقيق التوازن بين فوائد ومخاطر العملة الرقمية للبنوك المركزية من خلال تحديد تصميم فني دقيق يعتمد على خصائص كل اقتصاد وقطاعاته المالية. كلمات دالة: عملة رقمية للبنك المركزي، سياسة نقدية، بنك مركزي، عملة مشفرة، لامركزية المعاملات. Abstract: This Research Skillfully Paper Reach To Shed The Goals Light On The Competition Of Central Banks In Adapting To The New Form Of Digital Currencies In The Light Of The Encrypted Economy, As Well As The Implications Of The Adoption Of The Central Bank’s Digital Will Currencies On Monetary, Financial Intermediation And Financial Stability. The Study Of Us, We Have Adopt The Descriptive And Analytical And Concluded With The Most Important Results Of The Necessity To Invent A Balance Between The Beneficial) And Dangerous Of The Digital Currency For Central Banks By Defining An Accurate Technical Design That Depends On The Characteristics Of Each Economy And Its Financial Sectors. Key Words: Central Bank Digital Currency, Monetary Policy, Cryptocurrencies, Central Bank, Cryptocurrency, Decentralization Of Transactions.